Peranan Gerakan Pemuda Ansor Kecamatan Menganti dalam Meningkatkan Pembinaan Al-akhlaqul Karimah - Abdul Mu'id (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2019)
Youth is the spearhead of the nation's future, if the youth has the potential, then the country must become a developed country. As said by Imam Syafii, RA." For the sake of Allah, the life of youth is hung with knowledge and piety to Allah SWT., If both are not owned by a young man, then the existence of that youth will be dangerous. So youth who are not productive will have the potential to damage their own future, their family, society, religion, homeland and nation. Many youths who do not have knowledge and piety fall into liquor, (alcohol), adultery, drugs, gambling, prostitution, and theft. It is these negative activities that must be eliminated from the youth, youth, towards productive activities based on Faith, Knowledge and Taqwa.